Seroprevalence and Risk Factors for Toxoplasma gondii and Neospora caninum in Cattle in Portugal - Helga Waap; Andrea Bärwald; Telmo Nunes; Gereon Schares (Animals, 2022)
Neospora caninum has a worldwide economic impact as an important cause of abortion in cattle, while Toxoplasma gondii, another abortifacient pathogen, is globally a major foodborne zoonotic threat. The study aimed to evaluate the seroprevalence and risk factors for the two parasites in cattle in Portugal. A total of 612 sera from 35 farms were tested by an in-house p30 ELISA for T. gondii and p38 ELISA for N. caninum. T. gondii positive and suspicious sera were confirmed by p30 Western blot or IFAT. T. gondii and N. caninum animal seroprevalence was 9.2% (95%CI 7.1–11.7) and 17.2% (95% CI 14.4–20.4) and herd seroprevalence was 51.4% (95% CI 35.6–67.0) and 68.6% (95% CI 52.0–81.5), respectively. At the univariable level, climate area and precipitation of wettest month, driest month, driest quarter, and warmest quarter were significant predictors of seropositivity for both. N. caninum seropositivity was more likely in the region Norte, densely populated areas, and intensive production, and the probability of T. gondii seropositivity decreased with herd size. Results confirm the need to consider neosporosis in the differential diagnosis of cattle reproductive disorders in Portugal and may be valuable to inform source attribution models for human toxoplasmosis.